1993
DOI: 10.1080/1120009x.1993.11739200
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Action of Zn-Complexes on Herpes Simplex Virus Type 1 InfectionIn Vitro

Abstract: The influence of Zn-complexes with biologically active ligands like aminoacids: picolinic acid as Zn(pic)2 and asparaginic acid as Zn(asp)2 on HSV-1 infection in vitro was investigated. Studies on kinetics of Zn-ions using labeled 65Zn(pic)2 as a marker, show that at the 45th min Zn-ions are exposed onto or into cells. When cells were infected 60min after the treatment with 65Zn(pic)2, 1h later the activity of Zn-ions in the cell fraction decreased while in the medium increased. This result shows that soon aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…We have found that when copper, zinc or cobalt is bound to a suitable ligand, the appropriate complex exibited a significant anti-HSV effect (Varadinova et al, 1993;1996). Recently published data by Sagripanti et al (1997) also show that the inhibition of HSV by copper was enhanced by reducing agents and that mechanism of the inactivation is similar as for coppermediated DNA damage (Aruoma, et al 1991;Dizdaroglu, et al, 1991;Toyokuni and Sagripanti, 1994).…”
Section: Discussionmentioning
confidence: 74%
“…We have found that when copper, zinc or cobalt is bound to a suitable ligand, the appropriate complex exibited a significant anti-HSV effect (Varadinova et al, 1993;1996). Recently published data by Sagripanti et al (1997) also show that the inhibition of HSV by copper was enhanced by reducing agents and that mechanism of the inactivation is similar as for coppermediated DNA damage (Aruoma, et al 1991;Dizdaroglu, et al, 1991;Toyokuni and Sagripanti, 1994).…”
Section: Discussionmentioning
confidence: 74%
“…4, No. 1, 1997 Effect of Complexes of Zinc, Cobalt and Copper with D-Aminosugars on the Replication of Herpes Simplex v Virus Type 1 Zn(ll) with picolinic and with asp_artic acids are recommended (9).. In addition, the latter complexes.posses virucidal activity towards VZV virions, which is due to the virus-specific properties (11 ).…”
Section: Metal-based Drugsmentioning
confidence: 99%
“…Other agents used in therapy of VZV infection are Vidarabine and alpha-Interferon (9,10). Our previously published data have shown that Zn(pic) and Zn(asp)= inhibit key steps of H$Vreplication (11,12). However, the effect of these Zn-complexes on VZV infection in vitro is also of interest.…”
Section: Introductionmentioning
confidence: 87%